Is the evidence on the effectiveness of pay for performance schemes in healthcare changing? Evidence from a meta-regression analysis - Arezou Zaresani; Anthony Scott (BMC, 2021)
Abstract Background This study investigated if the evidence on the success of the Pay for Performance (P4P) schemes in healthcare is changing as the schemes continue to evolve by updating a previous systematic review. Methods A meta-regression analysis using 116 studies evaluating P4P schemes published between January 2010 to February 2018. The effects of the research design, incentive schemes, use of incentives, and the size of the payment to revenue ratio on the proportion of statically significant effects in each study were examined. Results There was evidence of an increase in the range of countries adopting P4P schemes and weak evidence that the proportion of studies with statistically significant effects have increased. Factors hypothesized to influence the success of schemes have not changed. Studies evaluating P4P schemes which made payments for improvement over time, were associated with a lower proportion of statistically significant effects. There was weak evidence of a positive association between the incentives' size and the proportion of statistically significant effects. Conclusion The evidence on the effectiveness of P4P schemes is evolving slowly, with little evidence that lessons are being learned concerning the design and evaluation of P4P schemes.